Changes in body dysmorphic disorder, eating disorder, and exercise addiction symptomology during the COVID-19 pandemic: A longitudinal study of 319 health club users. (April 2021) - Trott, Mike; Johnstone, James; Pardhan, Shahina; Barnett, Yvonne; Smith, Lee
Highlights: Exercise addiction scores significantly decrease pre vs post COVID-19 lockdown. Eating disorder symptomology significantly increased pre vs post COVID-19 lockdown. Body dysmorphic disorder incidence did not change pre vs post COVID-19 lockdown. Abstract: The aim of this longitudinal study was to examine the effect of COVID-19 quarantines on morbid exercise, eating, and body image behaviours pre vs post COVID-19 lockdown. Participants ( n =319; mean age 36.77 SD=11.75; 84% female) were recruited to complete a battery of questions with 14 month follow-up. Exercise addiction scores were significantly lower post-lockdown; eating disorder symptomology scores were significantly higher post-COVID-19 lockdown; and leisure-time exercise significantly increased post-COVID-19 lockdown. No differences in body dysmorphic disorder were found. If future lockdowns are enforced, practitioners working with people with suspected morbid eating habits should monitor this closely.